Investigating Customer Feedback Channels in the Hotel Industry: the Case of Ho – Ghana - Helen Mavis Dah; Arnold Dumenya (European Scientific Journal, ESJ, 2016)
Knowing what delight customers and satisfying them is highly critical for success in today’s competitive business environment. In order to satisfy customers and to meet their expectations, hotels must be able to understand customers’ needs and wants. Customer feedback provides invaluable information for organizations to re-orient their products and services. This study explores customer feedback channels that are used by hotels in Ho, Ghana and examines customers’ perceptions on the effectiveness of the feedback channels. Also, customers’ preferred channels were examined. Structured questionnaires were administered to 300 hotel guests at random. Out of the 300 questionnaires distributed, 171 were completed and used in the final analyses. Data was analyzed using SPSS version 22. The results revealed that suggestion box was mostly used by the hotels and guests perceived this channel as most effective among all other feedback channels. Also, guests preferred to provide feedback on one-on-one contact. The study concludes that developing effective customer feedback channels would motivate gueststo tell the hotel management about their satisfaction or dissatisfaction on the hotel services and products. Guest contact staff should be well trained in handling customer feedback and to possess good communication skills.